1998
DOI: 10.1083/jcb.140.5.1013
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Giantin in Docking COPI Vesicles to Golgi Membranes

Abstract: We have previously shown that p115, a vesicle docking protein, binds to two proteins (p130 and p400) in detergent extracts of Golgi membranes. p130 was identified as GM130, a Golgi matrix protein, and was shown to act as a membrane receptor for p115. p400 has now been identified as giantin, a Golgi membrane protein with most of its mass projecting into the cytoplasm. Giantin is found on COPI vesicles and pretreatment with antibodies inhibits both the binding of p115 and the docking of these vesicles with Golgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
250
1
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(265 citation statements)
references
References 40 publications
11
250
1
3
Order By: Relevance
“…This would be an attractive hypothesis, because it has been suggested that tethering may be linked to SNARE complex formation (64). However, amisyn is much smaller than the known tethering proteins like Uso1p (65), sec34p/sec35p (66), giantin (67,68), GM130 (69,70), and EEA1 (71). Thus, if amisyn were a tethering factor it would either tether membranes more closely than the above factors or be a component of a larger complex.…”
Section: Amisyn Coil Domain Inhibits the Rescue Of Exocytosis By Snapmentioning
confidence: 99%
“…This would be an attractive hypothesis, because it has been suggested that tethering may be linked to SNARE complex formation (64). However, amisyn is much smaller than the known tethering proteins like Uso1p (65), sec34p/sec35p (66), giantin (67,68), GM130 (69,70), and EEA1 (71). Thus, if amisyn were a tethering factor it would either tether membranes more closely than the above factors or be a component of a larger complex.…”
Section: Amisyn Coil Domain Inhibits the Rescue Of Exocytosis By Snapmentioning
confidence: 99%
“…However, COPI vesicles at every level are tethered to cisternae throughout the stack by flexible ''strings''-tethers that are long enough to permit vesicles to reach the adjoining cisternae on either side-effectively restraining transfers to the nearest neighbors in the stack (32,35). One system of strings, located at the cis face of the stack, has been well-characterized.…”
Section: Gos 28 Resides In the Same Copi-coated Buds And Vesicles Asmentioning
confidence: 99%
“…Tomosyn and p115 are of similar size and importantly contain a coiled-coil domain at their carboxyl termini that resembles the SNARE motif (66,67). p115 is thought to act as a tethering molecule by first linking Giantin on COP1-coated transport vesicles with the Golgi protein GM130 and subsequently promoting SNARE complex assembly on the target membrane (67,68). This role is consistent with the observation that expression of full-length Tomosyn was required to inhibit exocytosis, in vivo, and might indicate a separate but necessary role for the conserved aminoterminal domain of Tomosyn (18).…”
Section: Fig 7 Munc18c and B-tomosyn Binding To Syntaxin4 Is Not Mumentioning
confidence: 99%